Pelaksanaan Pendidikan Transformatif dalam Menghasilkan Pendidik Matematika yang Islami, Profesional, dan Kompetitif - Putri, Dini Palupi; Fitmawati, Fitmawati; Melita Sari, Sindi; Khasana, Ulfah; Oktapiyani, Lia (ARITHMETIC: Academic Journal of Math, 2021)
This study aims to analyze the implementation of transformative education in the Mathematics Education (Tadris Matematika) Study Program in producing Islamic, professional, and competitive mathematics educators. The sample in this research is Mathematics Education (Tadris Matematika) lecturers and students. Collecting data using observation, interviews, and documentation. The methods of data analysis used are reduction, display, and conclusion drawing and triangulation techniques. From this study, it was found that the implementation of transformative education in mathematics education (tadris matematika) study program was carried out by lecturers in producing Islamic, professional, and competitive mathematics educators. In producing Islamic educators, it is necessary to evaluate and improve again. In producing professional educators, the effort is still minimal, while the efforts of lecturers in producing competitive mathematics educators already exist through scientific writing competitions, but this has not had a good impact on producing competitive mathematics educators because most students are still insecure/lack of confidence in take part in competitions. The obstacles found are the lack of supporting infrastructure in professional development and the lack of self-confidence and motivation from students and lecturers. The contribution in this research is as an evaluation material for Mathematics Education (Tadris Matematika) lecturers, faculties in improving prospective Islamic, professional, and competitive mathematics educators in accordance with the vision and mission of the Mathematics Education (Tadris Matematika).